PENERAPAN KAPASITAS PRODUKSI OPTIMAL UNTUK PENGUATAN USAHA PENGOLAHAN ABON IKAN DAN BAKSO IKAN DI DUSUN GILI AIR, DESA GILI INDAH, KABUPATEN LOMBOK UTARA - Soraya Gigentika; Sitti Hilyana; Saptono Waspodo; Sadikin Amir (Jurnal Abdi Insani, 2023)
There are two fish processing and marketer groups in Gili Air Subvillage - Gili Indah Village. That group was formed in August 2021. Looking at the time they were created, the fish processing and marketer groups need assistance in carrying out fish processing production activities. The need for aid to the fish processing and marketer group is determining the optimal production capacity to plan processed fish production targets so that the fish processing business carried out provides maximum benefits. Assistance activities for fish processing and marketing groups in Gili Air Subvillage are carried out through educational and practical methods. Educational activities regarding setting targets for processed fish production capacity are carried out using active participatory action program methods in the field. Meanwhile, practical activities are carried out by gathering information based on participants' experiences. Based on the practice, it can be seen that the optimal production capacity carried out by the Putri Bahari group in processing fish floss is 1,200 kg per year. Meanwhile, the optimal production capacity carried out by the Lanter Gili group in processing fish balls is 920 kg per year. The results of the activities that have been carried out show that the fish processing and marketing groups in Gili Air Subvillage are willing to take advantage of the knowledge and information that has been provided in carrying out fish processing activities. This is based on the fact that the group needs to know the processing production capacity that will be produced in order to develop an appropriate strategy to generate optimal profits, there is a strategy in designing fish raw materials that need to be provided, the amount of packaging, and the division of work time.